Analysis of Employee Satisfaction and Performance Based On The Characteristics Of Compensation Systems and Organizational Culture in Hospital dr. Soepraoen Malang - Slamet Suhariyono, Untung (Journal for Research in Public Health, 2019)
This study aims to determine the effect of Employee Satisfaction and Performance based on the Characteristics of Compensation Systems and Organizational Culture in the Hospital of Dr. Soepraoen Malang. This study uses a quantitative research method research design. Data collected using a questionnaire on 100 permanent employee respondents at Soepraoen Hospital Malang.Independent variables of this study are Job Satisfaction and Employee Performance. The dependent variable of this study is the Compensation System and Organizational Culture. The results of the study show (1) Employee satisfaction has a significant influence on the compensation system; (2) Organizational culture has a significant influence on employee satisfaction; (3) Compensation has a significant influence on employee performance;(4) Organizational culture has a significant influence on employee performance; (5) Compensation has a significant effect on employee performance through employee performance satisfaction at the Hospital. II dr. Soepraoen; (6) Organizational culture has a significant influence on employee performance through employee performance satisfaction at the Tk Hospital. II dr. Soepraoen.